2013
DOI: 10.4038/sljv.v3i1.5410
|View full text |Cite
|
Sign up to set email alerts
|

On the way towards zero discrimination; What do people living with HIV think?

Abstract: Background: Sri Lanka is a country with a low prevalence of HIV infection. Nevertheless, number of people infected with HIV continues to rise with a considerable gap between the number identified and estimated. It is well known that stigma and discrimination to people living with HIV play a major role preventing people accessing services for HIV testing, care and support, worldwide.Sri Lanka is no exception. Methods: We interviewed 102 HIV patients using an interviewer administered questionnaire. In depth inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[6] Correct knowledge and attitudes of Nursing students on HIV and AIDS are very essential as they will be the nurses in the future. [7,8] Many studies have been done in several parts of the world to assess the knowledge of HIV/AIDS of nurses and nursing students. A study conducted in Calcutta shows that the majority of nursing student had inadequate knowledge and misconceptions especially with relate to the pathogenicity of HIV/AIDS, mode of transmissions, methods of prevention and signs and symptoms of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Correct knowledge and attitudes of Nursing students on HIV and AIDS are very essential as they will be the nurses in the future. [7,8] Many studies have been done in several parts of the world to assess the knowledge of HIV/AIDS of nurses and nursing students. A study conducted in Calcutta shows that the majority of nursing student had inadequate knowledge and misconceptions especially with relate to the pathogenicity of HIV/AIDS, mode of transmissions, methods of prevention and signs and symptoms of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In Sri Lanka, researchers found that considerable discrimination of PLHIV seems to take place at healthcare institutions. [7] A study on nursing officers indicated that fear of HIV transmission is one of the reasons for stigmatizing patients with HIV. [8] Like many other countries, in Sri Lanka, nurses are deeply involved in compassionate nursing care.…”
Section: Introductionmentioning
confidence: 99%